How Much Does WAIS-IV Perceptual Reasoning Decline Across the 20 to 90-Year Lifespan When Processing Speed is Controlled?. Issue 2 (4th March 2017) - Scheiber, Caroline; Chen, Hsinyi; Kaufman, Alan S.; Weiss, Lawrence G.
ABSTRACT: The most prominent pattern of cognitive change over the lifespan centers on the difference between patterns of maintained abilities on tests of crystallized knowledge and patterns of steady decline on tests of problem solving and processing speed. Whereas the maintained-vulnerable dichotomy is well established in the literature, questions remain about cognitive decline in problem solving when processing speed is controlled. This relationship has been examined in cross-sectional studies that typically used non-clinical tests with non-representative samples of adults. This study extended these findings to the most popular clinical test, the Wechsler Adult Intelligence Scale −4th ed. (WAIS-IV), using its carefully stratified sample as the source of data (ages 20-90 for Indexes, ages 16–90 for Perceptual Reasoning subtests). Multivariate Analysis of Covariance (MANCOVA) revealed that 70–80% of the variance in declining reasoning ability was shared with the speed factor. This was true (a) on the index and subtest level and (b) regardless of the type of problem-solving task employed. Such robust findings have important clinical and research implications for neuropsychologists, who most frequently use the Wechsler scales as part of their assessment battery.